A study of the mechanical strength of miniscrews and miniplates for skeletal anchorage - Pei-Chen Lu; Chau-Hsiang Wang; Huang-Chi Wang; Kun-Tsung Lee; Huey-Er Lee; Chun-Ming Chen (Elsevier, 2011)
Background/purpose: The concept of miniscrews-miniplates has been used in orthodontic practice to reinforce skeletal anchorage. The aim of this study was to evaluate the mechanical strength of miniplates in vertical and horizontal pull-out tests. Materials and methods: The insertion torques and pull-out strengths of 10 miniscrew-miniplate orthopedic sets (five for the vertical and five for the horizontal pull-out tests) within synthetic bone were determined. Each miniscrew-miniplate orthopedic set was composed of one miniplate and two 7-mm miniscrews, which were manually driven into the artificial bone. Insertion torque values and the vertical and horizontal pull-out strengths were measured. The Kruskal-Wallis test was used to test for significant differences. Results: The horizontal pull-out strength (mean, 233.1 N cm) was significantly greater than the vertical pull-out strength (mean, 106.8 N cm). The mean peak level of breaking force of the power chain was only 21.9 N cm. There was no significant relationship between the insertion torque and pull-out strength. Conclusions: Successful outcomes were confirmed for the skeletal anchorage concept for orthodontic treatment using miniscrews and miniplates. The mechanical strength of the miniscrews and miniplates was studied to prove the stability of fixation to resist orthodontic forces in the vertical and horizontal directions.